Diagnostic Laparoscopy as Decision Tool for Re-recurrent Inguinal Hernia Treatment Following Open Anterior and Laparo-Endoscopic Posterior Repair - Köckerling, Ferdinand; Schug-Pass, Christine (Frontiers in Surgery, 2017)
Introduction The guidelines of the international hernia societies recommend posterior repair in laparo-endoscopic technique for recurrent inguinal hernia after open anterior mesh repair and, conversely, open anterior repair for recurrence after laparo-endoscopic primary repair. Even when these guidelines are followed, already one year after repair a re-recurrence rate of 1–2 % must be expected, with that rate rising further in the subsequent years. Accordingly, increasingly more patients with re-recurrence after anterior and posterior mesh implantation must be treated. That constitutes a problem that to date has been investigated in only very few studies. Hence, there are no well-founded recommendations. This paper now presents a number of case reports aimed at identifying the role of explorative laparoscopy as decision tool for re-recurrent inguinal hernia treatment. Patients and Methods Based on three case reports the role of explorative laparoscopy as decision tool for re-recurrent inguinal hernia treatment is presented below. Results In all the three cases described explorative laparoscopy played a key role as decision tool when deciding how best to treat re-recurrence after anterior and posterior inguinal hernia repair. In one case severe adhesions after robotic prostatectomy and in another case correct placement of the mesh in the posterior plane, adhesions from the caecum to the groin region and no definitive finding of a re-recurrence resulted in an open repair. In the third case an insufficient laparoscopic posterior mesh placement made the re-recurrent TAPP procedure relatively easy. Conclusion Explorative laparoscopy is an important decision tool for re-recurrent inguinal hernia treatment to minimize the risks of the procedure for the patients.